Breastfeeding experience of postnatal mothers separated from preterm infants after discharge: a phenomenology qualitative approach - Xin Jiang; Hui Jiang; Shan Shan Shan; Rong Huang (BMC, 2024)
Abstract Background Breastfeeding practices are influenced by the maternal-infant bond relationship. Mothers of preterm infants in the puerperium face many challenges and support is needed to maintain breastfeeding after hospital discharge. This study explored the breastfeeding experiences among mothers of preterm infants and challenges that influenced their breastfeeding practices. Methods A qualitative phenomenological approach was used involving the mothers of preterm infants during the puerperium in Shanghai who fulfilled the inclusion criteria and consented to participate in the study. The mothers were recruited using purposive sampling. Eighteen participants were interviewed using semi-structured in-depth interviews. All interviews were recorded in digital audio, transcribed verbatim, and analyzed using thematic analysis. Findings The breastfeeding experience among mothers of preterm infants included four themes: breastfeeding motivation, breastfeeding challenges, breastfeeding support and education, and response to parental stress. Breastfeeding challenges included perceived insufficient milk, bottle preference, and maternal-infant separation. Two sub-themes of breastfeeding support included breastfeeding knowledge and approach. Conclusion To overcome breastfeeding challenges and improve the breastfeeding rate of preterm infants after discharge, medical professionals must develop individualized breastfeeding plans based on a comprehensive assessment of the needs of mothers who delivered a preterm infant.